(untitled) (The Batuk, 2020)
In the current business world, humans are considered as the success factor for any business. For this reason, reputed business firms are trying to hire the best human resource that is available in the market so that the firms can maintain its image and goodwill in the future as well. This study is based on the impact of performance appraisal on organizational performance of service sector institutions consisting of hospitals of Nepal. It is found that the performance appraisal systems have positive correlation with organizational performance. Regression coefficients of performance appraisal positively contribute to organizational performance explained by employee commitment, quality work life and work flexibility. It means that if Nepalese service sector invests a significant amount and effort for development of proper performance appraisal system, it can improve organizational performance.